A multi-locus perspective reveals connections between island biogeography and evolutionary history of an endangered shrew (Sorex pribilofensis) - Wiens, Benjamin J. (Kansas State University, 2021)
Accelerating anthropogenic environmental change poses numerous threats to mammalian wildlife. Island endemics are among the most vulnerable species to rapid environmental change, and account for a disproportionate amount of all documented extinctions. The current vulnerability of island species to global change is a result of their unique evolutionary ecology. The evolutionary forces of natural selection, genetic drift, and reduced or non-existent gene flow lead to the high levels of endemism on islands, but can also leave these species vulnerable to change. It is therefore vital for island biodiversity conservation that we understand how past environmental change has influenced evolutionary dynamics. Islands in the Bering Sea represent a classic system of land-bridge insular evolution. Through Quaternary climate cycling, oscillating sea levels have alternately connected Alaska and Siberia through the Bering Isthmus, and today the Arctic is experiencing climate change at a more rapid pace than lower latitudes. St. Paul Island, home of the endemic Pribilof Island Shrew (Sorex pribilofensis), is located in the southern Bering Sea and has been isolated from the mainland for ~14,000 years. This shrew is part of a diverse sibling species-complex, which has a wide-ranging Holarctic distribution. The goals of my thesis are to (1) resolve the evolutionary relationship of S. pribilofensis to other related shrews, and (2) clarify the evolutionary processes leading to speciation among these enigmatic mammals. Using a tiered genomic dataset of microsatellites, a maternally inherited mtDNA gene, and ~11,000 nuclear SNPs, I tested predictions related to the evolutionary and demographic history of S. pribilofensis. Given small island size and extended isolation, my overarching prediction was that genetic drift has led to rapid speciation and loss of genetic diversity within this shrew. In my first chapter, I show that S. pribilofensis is highly differentiated from sibling taxa using Discriminate Analysis of Principle Components and Structure clustering analyses. With phylogenetic analysis I then show that S. pribilofensis is the first to have diverged from closely related sibling taxa, and use Bayes Factor Species Delimitation to support species-level differentiation. In my second chapter, I give evidence for substantially reduced genetic diversity and a smaller effective population size of S. pribilofensis compared to mainland species. Through multiple linear regressions, I then show that genetic differentiation is closely tied to reduced genetic diversity in this system of shrews. Finally, compared to mainland sibling shrews, S. pribilofensis is most strongly differentiated at its least variable loci and least differentiated at its most variable loci. These combined results are indicative of strong genetic drift driving the differentiation of S. pribilofensis. Put together, my findings indicate a scenario whereby S. pribilofensis speciated rapidly after island isolation through neutral divergence, but in the process has lost much of its genomic diversity. These results highlight the potential for genetic drift, as a consequence of dramatic environmental change, to rapidly reshape island biodiversity while as a result potentially leaving island species less able to respond to multiple additional environmental stressors in an anthropogenic world.
Keywords: Evolutionary ecology; Island biogeography; Conservation genomics; Arctic biogeography; Genetic drift; Shrews